HUBUNGAN ANTARA PEMANFAATAN FASILITAS LABORATORIUM KIMIA DAN KEDISIPLINAN BELAJAR KIMIA DENGAN PRESTASI BELAJAR KIMIA SISWA KELAS XII IPA SMA NEGERI 1 SORONG - VINA N VAN HARLING; Markus Dwiyanto Tobi (LPPM Politeknik Saint Paul Sorong, 2019)
This study aims to determine: the significance of the relationship between the use of chemical laboratory facilities and student chemistry learning achievements; and the significance of the discipline of learning chemistry students with chemistry learning achievements. The populations in this study were students of class XII Science in SMA N 1 Sorong. A total of 97 students were taken using the Proportionate Random Sampling technique. The data collection methods used were questionnaires and documentation studies. The results showed that: 1) there was no positive and significant relationship between the use of chemical laboratory facilities and student chemistry learning achievements; and 2) there is no positive and significant relationship between the discipline of chemistry learning students and students' chemistry learning achievement.